(untitled) (International Journal of Engineering and Computer Science, 2023)
The proposed project is designed to monitor the environmental conditions such as Temperature, Humidity, Soil Moisture, Rain level and Light Intensity in order to monitor the conditions of agricultural farm land. Through this design the farmers can receive the informationin remote mode. The farmers can use this information as a reference to improve the agricultural productivity. When correct information is collected every day, the farmers can predict the problems and can take necessary precautions.